2014
DOI: 10.1002/esp.3544
|View full text |Cite
|
Sign up to set email alerts
|

Landscape response to tectonic and climatic forcing in the foredeep of the southern Apennines, Italy: insights from Quaternary stratigraphy, quantitative geomorphic analysis, and denudation rate proxies

Abstract: We present new data about the morphological and stratigraphic evolution and the rates of fluvial denudation of the Tavoliere di Puglia plain, a low-relief landscape representing the northernmost sector of the Pliocene-Pleistocene foredeep of the southern Apennines. The study area is located between the easternmost part of the southern Apennine chain and the Gargano promontory and it is characterized by several orders of terraced fluvial deposits, disconformably overlying lower Pleistocene marine clay and\ud or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 67 publications
(163 reference statements)
2
19
0
Order By: Relevance
“…Further, in the Middle Pleistocene to Holocene time span, low values of denudation rates (i.e. about 0.1 mm/yr) have recently been recognized in the northern sector of the Pliocene-Pleistocene foredeep of the southern Apennines on the basis of fluvial terrace chrono stratigraphy, supported by OSL and AAR dating (Gioia et al 2014). In this sector, Middle to Late Pleistocene uplift rates from the elevation of marine terraces are quite similar to the denudation rates, thus suggesting a near steady-state landscape.…”
Section: Uplift and Erosion Ratesmentioning
confidence: 91%
“…Further, in the Middle Pleistocene to Holocene time span, low values of denudation rates (i.e. about 0.1 mm/yr) have recently been recognized in the northern sector of the Pliocene-Pleistocene foredeep of the southern Apennines on the basis of fluvial terrace chrono stratigraphy, supported by OSL and AAR dating (Gioia et al 2014). In this sector, Middle to Late Pleistocene uplift rates from the elevation of marine terraces are quite similar to the denudation rates, thus suggesting a near steady-state landscape.…”
Section: Uplift and Erosion Ratesmentioning
confidence: 91%
“…Published data on the beginning of the morphogenesis of the central-southern Apennines (Bosi et al 1996;Ascione et al 1997Ascione et al , 2012Ascione et al , 2014Ascione & Cinque 1999;Basili et al 1999;D'Alessandro et al 2003;Schiattarella et al 2006Schiattarella et al , 2008Gioia et al 2014;Miccadei et al 2014) suggest that its internal portion gradually emerged during the Pliocene. Particularly, these authors have demonstrated that the emersion and, therefore, the beginning of the morphogenesis occurred gradually from the NW (Abruzzo-Molise sector) to SE (Campania-Lucania sector), between the Early -Middle Pliocene and the Lower Pleistocene.…”
Section: The Sw Sectormentioning
confidence: 99%
“…For the Apennines that are one of the youngest mountain chains in the world, these approaches have been successfully applied in several sectors of the central and southern Apennines (Brancaccio et al 1979(Brancaccio et al , 1988(Brancaccio et al , 2000Bosi et al 1996;Amato & Cinque 1999;Coltorti & Pieruccini 2000;Bartolini et al 2003;D'Alessandro et al 2003;Schiattarella et al 2003Schiattarella et al , 2006Coltorti et al 2005;Di Bucci et al 2005;Aucelli et al 2011;Amato et al 2014;Gioia et al 2014). With particular reference to the Molise sector of the Apennines, several studies have been conducted and published by our research group (Aucelli et al 2001(Aucelli et al , 2012Russo Ermolli et al 2010;Amato et al 2011Amato et al , 2012Amato et al , 2013Amato et al , 2014Bracone et al 2012a), while others are still in progress.…”
Section: Introductionmentioning
confidence: 99%
“…River down-cutting and development of "terraced surfaces" indicate a gradual lowering trend in the general base level of erosion. This trend is typical of areas affected by a widespread uplift trend (Ahnert 1970;Chappell 1974;Iwata 1987;Merritts & Hesterberg 1994;Burbank et al 1996;Abbott et al 1997;Whipple & Tucker 1999;Hovius 2000;Jamieson et al 2004;Ascione et al 2008;Walker et al 2011;Gioia et al 2014).…”
Section: Discussionmentioning
confidence: 81%